2019
DOI: 10.1002/jper.19-0060
|View full text |Cite
|
Sign up to set email alerts
|

Associations of electronic and conventional cigarette use with periodontal disease in South Korean adults

Abstract: Background The aim of this study was to examine the association of conventional cigarette smoking and electronic cigarette vaping with periodontal disease in South Korean adults. Methods For this study, data from 13,551 participants, a subset derived from the Korean National Health and Nutrition Examination Survey conducted between 2013 and 2015, were examined. Participants were divided into four categories: electronic cigarettes vapers, conventional cigarettes smokers, ex‐users, and non‐users. Periodontal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 35 publications
5
46
1
8
Order By: Relevance
“…Consistent with our findings, ENDS users were recently determined to be twice as likely to suffer from periodontal disease and three times as likely to have gingival disease than individuals that did not use ENDS or conventional cigarettes. 13,14 ENDS usage has also been demonstrated in studies to be associated with a number of oral symptoms such as dry mouth, irritation, bad breath, and others. 6 These oral symptoms related to ENDS use, however, have been shown to be reduced compared to conventional cigarette smoking.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, ENDS users were recently determined to be twice as likely to suffer from periodontal disease and three times as likely to have gingival disease than individuals that did not use ENDS or conventional cigarettes. 13,14 ENDS usage has also been demonstrated in studies to be associated with a number of oral symptoms such as dry mouth, irritation, bad breath, and others. 6 These oral symptoms related to ENDS use, however, have been shown to be reduced compared to conventional cigarette smoking.…”
Section: Resultsmentioning
confidence: 99%
“…More studies examining risk of CVD outcomes in PD, with adjustments for key confounders, are also required to permit robust meta‐analyses in the future. Recent research has demonstrated a strong association of electronic cigarette smoking and PD, with a higher risk of PD in people using e‐cigarettes compared to conventional cigarettes (Jeong et al, 2019). Smoking in addition to other risk factors such as stress should also be adjusted for in future analyses to ensure minimal confounding effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cessation plans could be better if parents and their adolescents quit together, as young people are heavily affected by their parents' smoking [18,24,25]. Moreover, government and public health professionals should engage in intensive efforts to reduce tobacco use, by developing tobacco control policies (e.g., legislation to ban smoking), media campaigns, educational exhibitions, and public service announcements [9,14,36,37]. Above all, it is important for adolescents to realize the need to quit smoking and be alert to this need.…”
Section: Discussionmentioning
confidence: 99%
“…Stopping tobacco use is often considered the most important element in cancer prevention worldwide [7][8][9]. However, smoking cessation programs have had limited success in South Korea, with many smokers unable to abstain from tobacco use for longer than a year [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation